Government-University Relations: 1MB or No 1MB? A Comparative View of Alberta and British Columbia - Southern, Lee; Dennison, John D. (Canadian Journal of Higher Education, 1985)
The concept of an intermediary body (1MB) between government and universities has often been debated in the literature of higher education in Canada. While much of the discussion has centred around the theoretical advantages for both organizations which would accrue from the establishment of an 1MB, there have been few attempts to assess whether these advantages occur in practice. This paper reports on the result of a study of government - university relations in Alberta and British Columbia. The major purpose was to analyse differences in matters of autonomy, budget allocation, and planning, existing between Alberta, which abolished its 1MB in 1972, and British Columbia, which has had a Universities Council since 1974. The results indicated very few differences between the two provinces in the matters under review. What did emerge, however, were some important requirements for the effective operation of universities during the financial realities of the eighties.